BK channel openers NS1619 and NS11021 reverse hydrogen peroxide-induced membrane potential changes in skeletal muscle. (2nd September 2020) - Coskun, Cagil; Buyuknacar, Hacer Sinem; Cicek, Figen; Gunay, Ismail
Abstract: Large conductance calcium-activated potassium (BK) channels play a crucial role in the repolarization and after-hyperpolarization phases of the cell membrane. The channel openers are also used in treatment of some diseases, including hypo/hyperkalemic periodic paralysis. However, little is known about the effects of BK channels and the channel activators on membrane potentials in skeletal muscle. In addition, the effects of reactive oxygen species (ROS) on BK channels in skeletal muscle are also unknown. Therefore, the aim of this study was to determine the effects of BK channel openers and ROS on membrane potentials in skeletal muscle fibers. For this purpose, resting membrane potentials and action potentials (AP) of frog gastrocnemius muscles were recorded in the presence of commonly used BK channel openers NS1619 and NS11021, H2 O2 (a type of ROS), and both using intracellular microelectrode technique. The channel activators significantly and dose-dependently decreased amplitude and increased rise time of AP but did not impact repolarization. The presence of H2 O2 plus NS1619 or NS11021 resulted in significant change because the channel openers completely reversed the deleterious effects of hydrogen peroxide on the repolarization phase of AP in skeletal muscle fibers. In the present study, the contributions of BK channel activation and the modulatory role of H2 O2 on membrane potentials was demonstrated in skeletal muscle fibers, for the first time. Moreover, it should be noted that BK channel openers should be used in the treatment of reactive oxygen species-induced skeletal muscle diseases.